Mission Possible: Creating a Spectacle with a Repetition of the Same Formula - Syamsi, Vera (Universitas Multimedia Nusantara, 2024)
A motion picture is one of the most popular spectacles people enjoy for various reasons, among others for entertainment. A film titled